China's Superbank : Debt, Oil and Influence - How China Development Bank is Rewriting the Rules of Finance - Sanderson, Henry (Bloomberg., 2012)
Inside the engine-room of China's economic growth-the China Development Bank Anyone wanting a primer on the secret of China's economic success need look no further than China Development Bank (CDB)-which has displaced the World Bank as the world's biggest development bank, lending billions to countries around the globe to further Chinese policy goals. In China's Superbank, Bloomberg authors Michael Forsythe and Henry Sanderson outline how the bank is at the center of China's domestic economic growth and how it is helping to expand China's influence in strategically important overseas markets.